2012
DOI: 10.1371/journal.pone.0034074
|View full text |Cite
|
Sign up to set email alerts
|

Water Availability Is the Main Climate Driver of Neotropical Tree Growth

Abstract: • Climate models for the coming century predict rainfall reduction in the Amazonian region, including change in water availability for tropical rainforests. Here, we test the extent to which climate variables related to water regime, temperature and irradiance shape the growth trajectories of neotropical trees. • We developed a diameter growth model explicitly designed to work with asynchronous climate and growth data. Growth trajectories of 205 individual trees from 54 neotropical species censused every 2 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
95
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 77 publications
8
95
0
6
Order By: Relevance
“…wood production, in tropical forests have been highlighted in most longterm permanent plots (Nepstad et al, 2002;Stahl et al, 2010;Wagner et al, 2012), even under very stable climate conditions (O'Brien et al, 2008;Clark et al, 2010). This seasonality is obviously linked to the intra-annual variation of cambial activity that has been reported in various environments, from dry (Worbes, 1999;Enquist and Leffler, 2001;Lisi et al, 2008) to flooded forests (Schongart et al, 2002), but also in more mesic environmental conditions (Fichtler et al, 2003;Clark et al, 2010).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…wood production, in tropical forests have been highlighted in most longterm permanent plots (Nepstad et al, 2002;Stahl et al, 2010;Wagner et al, 2012), even under very stable climate conditions (O'Brien et al, 2008;Clark et al, 2010). This seasonality is obviously linked to the intra-annual variation of cambial activity that has been reported in various environments, from dry (Worbes, 1999;Enquist and Leffler, 2001;Lisi et al, 2008) to flooded forests (Schongart et al, 2002), but also in more mesic environmental conditions (Fichtler et al, 2003;Clark et al, 2010).…”
mentioning
confidence: 93%
“…Current studies performed in tropical rainforests have highlighted three major climate drivers of secondary growth, rainfall, solar irradiance and air temperature: (i) rain or lack of rain is often implicitly viewed as the main driver of rainforest dynamics (Phillips et al, 2009), as annual net primary production (NPP) generally positively correlates with the annual amount of precipitation (Tian et al, 1998). Recently, Wagner et al (2012) showed that rainfall seasonality plays a key role in the tropical forests' response to climate variability. (ii) Irradiance is directly linked to plant photosynthetic capacity, in turn driving carbon uptake and plant growth (Graham et al, 2003).…”
mentioning
confidence: 99%
“…In addition to nutrients, water availability can be responsible for over 60 % of the environmental effect on tree growth (Wagner et al, 2012). In this study, we hypothesized that the growth of saplings in the forest understory is limited by both sunlight and the availability of soil nutrients, and that variations in soil water content across rainfall seasons infl uence photosynthesis and sapling growth.…”
Section: Introductionmentioning
confidence: 99%
“…Its vegetation stores about 90 Pg (1 Pg = 10 15 g) of carbon (Saatchi et al, 2007), and about 50 % of the rainfall in the region comes from water cycled via transpiration (Salati, 1987;Fisher et al, 2009). Net productivity of tropical forests may be limited by several factors, including nutrient defi ciency (Vitousek et al, 2010), sunlight (Graham et al, 2003) and soil water content (Wagner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Já Worbes et al (2003), analisando os anéis de crescimento do tronco, descreveram diferentes padrões de crescimento para diferentes espécies: espécies com curva de crescimento sigmoidal (crescimento constante na fase juvenil, com aumento da taxa de crescimento na maturidade e redução na fase final do ciclo de vida); espécies com curva exponencial de crescimento por toda a vida; e as que não apresentavam padrões identificáveis. Mais recentemente, análises do crescimento das árvores vêm sendo empregadas para compreensão das respostas das espécies diante das mudanças climáticas, ocasionadas por ações antrópicas ou naturais, na tentativa de prever alterações na estrutura florestal decorrentes dessas novas condições (CLARK et al, 2010;WAGNER et al, 2012). Assim, a avaliação do CCT do tronco das árvores pode ser uma forma de caracterizar a autoecologia das espécies e o funcionamento de florestas, contribuindo para o manejo adequado e o sucesso de reflorestamentos em cenários futuros (KREPKOWSKI et al, 2011).…”
Section: Introductionunclassified